A study on factors of Bandera’s social learning theory towards change of behaviour to determine performance among SIMA trainees in Standard Chartered Bank / Norhidayati Basiron @ Basiran - Basiron @ Basiran, Norhidayati (Faculty of Business and Management, 2010)
SIMA (Scope International Malaysia Academy- Standard Chartered Bank) is an institution that provide training for internship and fresh graduated for three and half month. All trainees will be divided into five departments such as International Trade, Securities Services, Forex and Money Market’s (FMO), Credit and Risk Control (CRC), and Client Services Group (CSG). The problem of this study is most of the trainees remain silence instead of asking their co-workers. Objective of this study is to study a change of behaviour among the trainees and find the factors that influence the behaviour change. Based on the finding, all variables are not significant and all hypotheses are rejected and this is due to lack of other factors and limitation sampling size. The researcher suggested for future researcher to take other factors that influence the change of behavior and maximize its sampling size or scope of study.